(untitled) (Ameghiniana, 2013)
Two species of the genus Hyolitbes Eichwald (1840), one new (H. amosi) and another nomina aperta are described and figured. Their relations with known species are also established. The material was found with other molluscs in the Upper Paleozoic exposures (Tepuel Group) in the Tepuel and Languiñeo Hills, Chubut Province (Rep. Argentina).